KERJASAMA UNIVERSITAS RIAU DAN UNIVERSITAS KYOTO DALAM PENGELOLAAN EKOSISTEM GAMBUT DI KABUPATEN BENGKALIS TAHUN 2010-2014 - Hasma Al Husna Al Husna; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explains about cooperation of Riau University and Kyoto University forward management of peatland ecosystem in District Bengkalis-Indonesia. The purpose of this research to know degradation of peatland ecosystem in District Bengkalis-Indonesia have global effect. A huge of peat area unwise exploited, especially for palm oil plantation industrial forest estate (plantation development: forestry and estate corps). This problem have of interest to the international institutions do research of peat, one of it’s Kyoto University. Kyoto University have partnership with Riau University. This research is a qualitative research. Method applied in doing this research is descriptive analysis with aim to depict and analyzed a phenomenon in this case. By using the Pluralism perspective to analyze the role of non state actor and global issue not only limited in security case and military case but international politics agenda very large. Cooperation theory to analyze how human necessities increase and interdependence complex required every state to cooperate. The result of show that peatland degradation have global effect. Parties exploit in this case which is economic interest with do in the name of environment issue. Research of Riau University and Kyoto University give solution for peatland problem with strategy and applied policy sustainable management of peatland ecosystem to reduce the risk of fire and associated regional haze. Also identified were actions (related to research, industry or local management practice or policies) need from different stakeholders, such as local governments, companies, NGOs, communities and researchers, to reduce or resolve the problem of peatland degradation in different scenarios. Keyword: international cooperation, peatland, and sustainable management